Quality analysis of the defect location information in transmission line outages caused by fires - Tito Ricardo Vaz da Costa; Ailton Teixeira do Vale; Clarissa Melo Lima; Joaquim Carlos Goncalez (International Journal of Applied Power Engineering (IJAPE), 2023)
This paper analyzed the quality of the information regarding power outages caused by fires in the Brazilian transmission system in the years 2018 and 2019. Six transmission line trunks with asymmetrical performance regarding fire-related outages in the period were selected. The selected trunks correspond to twelve 500 kV transmission lines with a total length of 3,998 km. Outage, geospatial transmission line data and fire outbreak information was compared for twelve transmission lines of interest, all located in regions with a high incidence of fires. The results suggest that the data provided by the transmission line fault locating equipment is not accurate when compared to the fire outbreak data provided by satellites.